Desenvolvimento de metodologia de análise e indução à produção de alcalóides espiroquinazolinos por Eupenicillium SP - Barros, Fabio Alessandro Proença (2006)
It is presented the development of a liquid chromatography-UV-tandem mass spectrometric method for spiroquinazolinic alkaloids analyses in a variety of matrices where the fungus Eupennicilium sp. was cultivated. Sample preparation was conducted using a solid-phase extraction stratergy. These rare alkaloids were isolated from Eupenicillium sp an endophitic fungi obtained from Murraya paniculata (RUTACEAE). The fungus when cultivated in corn and rice subtracts produces spiroquinazolines alkaloids that exhibit high important activities, mostly analgesic. The structures of these alkaloids are formed by a sequence of amino acids similar to these carbazolic alkaloids produced by Murraya plants, which might explain some aspects of the microrganism-plant interaction. The analytical methodology was used in experiments to determine the amount of these alkaloids produced over cultivativation time. Biogenesis investigation was performed to obtain data useful to increase alkaloid production. Three unprecedented spiroquinazoline alkaloids were identified and characterized using 1D and 2D RMN together with MS and MSMS experiments.